Synthesis and complexation of new unsymetrical 1,2-dihydroxyimino-3,7-diaza-8-phenyloctane - Sekerci, M (Marcel Dekker Inc, 1999)
vic-Dioximes have great importance since they are used as chelateing agents because of their stable complexes with transition metals. 1-Amino-3-(N-benzylamino)propane (1) has been obtained by the reaction of benzyl chloride and 13-diaminopropane. In a second step 1,2-dihydroxyimino-3,7-diaza-8-phenyloctane (2) has been obtained by the reaction of (1) with anti-chloroglyoxime. The resulting 1,2-dihydroxyimino-3,7-diaza-8-phenyloctane ligand was reacted with transition metal salts, such as Ni(II), Co(II) and Cu(II). The Cu(II) and NI(II) complexes of these ligands are proposed to be square-planer, while the Co(II) complexes are proposed to be octahedral with water molecules as axial ligands. The structures of the new materials were identified by elemental analyses, infrared and H-1 NMR spectra, magnetic measurements, TGA and DTA techniques.
Keywords: Amine Oxime Ligands; Molecular-Structure; Metal Complexation; Crystal-Structures; Nickel(Ii); Cobalt(Ii); Palladium(Ii); Copper(Ii); (E,E)-Dioximes; Platinum(Ii)